Antiinflammatory effects of the phosphodiesterase-4 inhibitor cilomilast (Ariflo) in chronic obstructive pulmonary disease. - Gamble, E; Grootendorst, D; Brightling, C; Troy, S; Qiu, Y; Zhu, J; Parker, D; Matin, D; Majumdar, S; Vignola, A; Kroegel, C; Morell, F; et al. (2003)
Cilomilast (Ariflo), a new oral phosphodiesterase-4 selective inhibitor, improves lung function in chronic obstructive pulmonary disease (COPD). We have evaluated its antiinflammatory effects in 59 patients with COPD randomized to receive cilomilast, 15 mg two times a day, or placebo for 12 weeks. Induced sputum differential cell counts were obtained at baseline and at five further visits. Interleukin-8 and neutrophil elastase were measured in sputum supernatant. Bronchial biopsies obtained at baseline and at Week 10 were immunostained and counted for neutrophils, CD8+ and CD4+ T-lymphocyte subsets, and CD68+ macrophages. Cells expressing the genes for interleukin-8 and tumor necrosis factor-alpha were identified by in situ hybridization and quantified. Compared with placebo, analysis of variance (ANOVA) of the change from baseline showed that cilomilast did not alter any sputum endpoint or FEV1. However, bronchial biopsies demonstrated that cilomilast treatment was associated with reductions in CD8+ (p = 0.001; ANOVA) and CD68+ cells (p < 0.05; ANOVA). In addition, by Poisson analysis, comparison of cell counts analyzed as a ratio of active to placebo demonstrated reductions of CD8+ (48% p < 0.01) and CD68+ (47% p = 0.001) cells. This is the first demonstration of reduction by any agent of airway tissue inflammatory cells characteristic of COPD. Phosphodiesterase-4 inhibitors represent a promising new class of substances for use in antiinflammatory treatment of this disease.